2021
DOI: 10.1007/s12080-021-00522-w
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary rescue can prevent rate-induced tipping

Abstract: The transformation of ecosystems proceeds at unprecedented rates. Recent studies suggest that high rates of environmental change can cause rate-induced tipping. In ecological models, the associated rate-induced critical transition manifests during transient dynamics in which populations drop to dangerously low densities. In this work, we study how indirect evolutionary rescue—due to the rapid evolution of a predator’s trait—can save a prey population from the rate-induced collapse. Therefore, we explicitly inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 92 publications
(113 reference statements)
0
12
0
Order By: Relevance
“…In recent years, for example, it has been observed that a time-dependent transition connecting a past dynamical system to a future one can give rise to critical transitions when the transition dynamics "fails to connect the limit ones" [5]. This type of phenomenon has been identified in several real scenarios including ecology [39,42], climate [2,5,27,43], biology [21], and quantum mechanics [23], among others.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, for example, it has been observed that a time-dependent transition connecting a past dynamical system to a future one can give rise to critical transitions when the transition dynamics "fails to connect the limit ones" [5]. This type of phenomenon has been identified in several real scenarios including ecology [39,42], climate [2,5,27,43], biology [21], and quantum mechanics [23], among others.…”
Section: Introductionmentioning
confidence: 99%
“…sudden dramatic changes in population size, generally toward much lower numbers) has been well-explained in models with bistability between two stationary base states (Dakos et al, 2019). These two states could be, for example, a high population coexistence state and either a low population coexistence state or a state with extinction of one or both populations (Kaur & Sharathi, 2022;O'Keeffe & Wieczorek, 2019;Osmond & Klausmeier, 2017;Vanselow et al, 2019Vanselow et al, , 2022. However, little is known about the effects of climate change on systems whose base state is oscillatory (Bathiany et al, 2018;Sauvé et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have considered how evolution can counteract deleterious environmental change [22][23][24][25][26], yet the body of work on rate-induced tipping points has so far developed independently. An exception is the recent work by Vanselow et al [27], which shows that rate-induced collapse of a prey population occurring purely due to the ecological dynamics (i.e. even with no evolution) can be indirectly prevented through the evolutionary adaptation of a predator population.…”
Section: Minimal Model Of Evolutionary Rescue and Rate-induced Extinc...mentioning
confidence: 99%